Effectiveness of Mulligan’s Two-Leg Rotation Versus Muscle Energy Technique in Subjects With Hamstring Tightness - Jaiswal, Pratik R; Qureshi, Irshad; Phansopkar, Pratik A (Curēus (Palo Alto, CA), 2022)
BackgroundHamstring stiffness has been growing more common, but is often neglected. The hamstring muscle complex is the key and most commonly involved muscle group for stiffness, and the younger generation is particularly susceptible. The tightness causes a limited range of motion and associated consequences. The purpose of this study is to look for the efficacy of Mulligan’s two-leg rotation (TLR) and muscle energy technique (MET).MethodsTo evaluate TLR against MET, an intervention with a duration of six days per week was planned. Modified Oswestry disability questionnaire (MODQ), active knee extension (AKE), lumbar range of motion (LROM), and numerical pain rating scale (NPRS) were used as outcome measures. The duration of the study was six months. It is a pre and post-interventional type of study.ResultStatistical analysis was done by using descriptive and inferential statistics using Student’s paired and unpaired t-tests. The Statistical Package for Social Sciences (SPSS) version 27 (IBM Corp., Armonk, NY, USA) was used. A p-value <0.05 was considered significant. Both the treatment protocol were beneficial for the patients but TLR yields a more significant reduction in tightness and pain than MET.ConclusionThe results after the data analysis show that TLR should be utilized for individuals with hamstring tightness because it exhibited a significant reduction in tightness and pain when compared to MET.